2020
DOI: 10.1007/s10639-020-10379-x
|View full text |Cite
|
Sign up to set email alerts
|

Effective measures to foster girls’ interest in secondary computer science education

Abstract: The interest of girls in computing drops early during primary and secondary education, with minimal recovery in later education stages. In combination with the growing shortage of qualified computer science personnel, this is becoming a major issue, and also a target of numerous studies that examine measures, interventions, and strategies to boost girls’ commitment to computing. Yet, the results of existing studies are difficult to navigate, and hence are being very rarely employed in classrooms. In this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 27 publications
2
32
0
Order By: Relevance
“…However, these antecedents have yet to be summarized systematically, and more review articles are needed. Third, prior research has pointed out differences between male and female students' STEM career interests (Happe et al, 2021). Also, children's coding experience may change their gender-based stereotypes or perceptions of STEM careers (Bati et al, 2021).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…However, these antecedents have yet to be summarized systematically, and more review articles are needed. Third, prior research has pointed out differences between male and female students' STEM career interests (Happe et al, 2021). Also, children's coding experience may change their gender-based stereotypes or perceptions of STEM careers (Bati et al, 2021).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…• Gender-gap: A closely related challenge is finding strategies for the mitigation of gender gap, a problem for the vast majority of computer science degrees (Happe et al, 2021).…”
Section: Research Goalmentioning
confidence: 99%
“…In order to find out what the latest research has revealed about what keeps women from the IT field, a dozen review papers, published in the past two years, were selected. [9,10,11,12,13,14] After examining these recent papers, each dedicated to review the latest literature about young women's barriers, we can differentiate four basic obstacles that account for girls' scarcity in IT: social, selfefficacy, educational, and labour market factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The most fundamental obstacle that girls face is gender stereotyping, that is, a binary world view that divides the social world into feminine vs. masculine domains and characteristics [15] connecting IT, and generally, STEM 1 to masculinity. [9,10,11,12,13,14] Gender-based social stereotypes can affect how young women's closest environment relates to their career interests, such as their families. It is especially fathers' and male siblings' attitudes that were shown to influence girls' choices.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation